PIK3R1Met326Ile germline mutation correlates with cysteine-rich protein 61 expression and poor prognosis in glioblastoma - Yoshihiro Otani (Nature Portfolio, 2017)
Abstract Despite therapeutic advances, glioblastoma represents a lethal brain tumor. Recently, research to identify prognostic markers for glioblastoma has intensified. Our previous study demonstrated that median progression-free survival (PFS) and overall survival (OS) of patients with high cysteine-rich protein 61 (CCN1) expression was significantly shorter than that of patients with low CCN1 expression. To understand the molecular mechanisms that regulate CCN1 expression, we examined 147 tumour samples from 80 patients with glioblastoma and 67 patients with lower grade glioma. Next-generation and Sanger sequencing showed that PIK3R1Met326Ile was more frequent in the CCN1 high expression group (10/37 cases, 27.0%) than the CCN1 low expression group (3/38 cases, 7.9%) in glioblastoma. This mutation was also detected in corresponding blood samples. In multivariate analysis, high CCN1 expression and PIK3R1Met326Ile in glioblastoma patients were prognostic factors for OS [HR = 2.488 (1.298–4.769), p = 0.006] and [HR = 2.089 (1.020–4.277), p = 0.0439], respectively. Thus, the PIK3R1Met326Ile germline appears to be correlated with CCN1 expression and poor prognosis in glioblastoma.